Development of a ground-based sensorimotor disorientation analog to replicate astronaut postflight experience - Moudy, Sarah C.; Peters, Brian T.; Clark, Torin K.; Schubert, Michael C.; Wood, Scott J. (Frontiers in Physiology, 2024)
The perceptual and motor coordination problems experienced following return from spaceflight reflect the sensory adaptation to altered gravity. The purpose of this study was to develop a groundbased analog that replicates similar sensorimotor impairment using a standard measures test battery and subjective feedback from experienced crewmembers. This Sensorimotor Disorientation Analog (SDA) included varying levels of sensorimotor disorientation through combined vestibular, visual, and proprioceptive disruptions. The SDA was evaluated on five previously flown astronauts to compare with their postflight experience and functional motor performance immediately (Return (R)+0 days) and +24 hours (R+1) after landing. The SDA consisted of galvanic vestibular stimulation (GVS), visual disruption goggles, and a weighted suit to alter proprioceptive feedback and replicate perceived heaviness postflight. Astronauts reported that GVS alone replicated ~50-90% of their postflight performance with the weighted suit fine-tuning the experience to replicate an additional 10-40% of their experience. Astronauts did not report feeling that the disruption goggles represented either the visual disruptions or illusory sensations that they experienced, nor did they impact motor performance in postflight tasks similarly. Based on these results, we recommend an SDA including the GVS and the weighted suit. These results provide a more realistic and portable SDA framework to provide transient spaceflight-relevant sensorimotor disruptions for use in countermeasure testing and as a pre-flight training tool.